Attractors of Differential Inclusions and Their Approximation - Valero, J.; Kapustyan, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the properties of solutions of differential inclusions in a Banach space. We prove a theorem on the existence of a global attractor for a multivalued semidynamical system generated by these solutions and a theorem on the approximation of an attractor in the Hausdorff metric.